Coaching for SOWL : self-other-world learning in global education - Rodriguez, Angela (Emerald Publishing Limited, 2025)
Global education and coaching are concerned with transformation. Both expand self-awareness and open new ways of being in a world of others in a moment characterized by unprecedented and rapid change. In global education, the emphasis is on learning to collaborate within difference and embrace a concern for the greater good. In coaching, the work focuses on cultivating new ways of understanding oneself, others and the world, and expanding habitual repertoires of choice and response. Coaching for SOWL: Self-Other-World Learning in Global Education bridges these fields, showing how coaching offers a uniquely appropriate modality for advancing our capacity to hear, hold and engage with difference, and to link personal and social transformation. By looking at coaching pedagogically, this book offers an approach that does two things. It allows global educators to reconsider how we make sense of encounters with others different from oneself. It also posits coaching as a tool to support those engaging in the important global work the world needs. Responding to an urgent need to foster environments that promote both personal growth and collective responsibility, Rodríguez provokes thoughtful inquiry into what the future is asking of us as global educators.